γ‐Cyclodextrin Nitrate/CL‐20 Complex: Preparation and Properties - Maksimowski, Paweł; Grzegorczyk, Agnieszka; Cieślak, Katarzyna; Gołofit, Tomasz; Chmielarek, Michał; Tomaszewski, Waldemar; Pawłowski, Wojciech (Propellants, explosives, pyrotechnics, 2019)
Gamma‐cyclodextrin/CL‐20 (γ‐CD/CL‐20) inclusion complex was prepared and characterized by infrared and 1H NMR spectroscopy. The study findings point to a weak interaction of CL‐20 protons with H3 and H5 protons, however relatively intense interactions with OH groups in a γ‐CD molecule, which allows to conclude that a CL‐20 molecule does not penetrate completely the toroid cavity formed by γ‐CD. The resulting complex was subject to nitration with 100 % nitric acid. Analysis of the 1H NMR spectrum demonstrated that an average of 21.6 OH groups in the starting γ‐CD underwent esterification. The nitrated complex is characterized by a higher density (1.81 g/cm3), and the sensitivity to impact (5 J) and friction (200 N) comparable to the starting complex. Thermogravimetric analysis of the nitrated γ‐Cyclodextrin/CL‐20 complex pointed to a two‐phase decomposition at 194 and 339 °C with a total significant exothermic effect amounting to 3230 J/g.